2016
DOI: 10.14390/jsshp.hrp2015-017
|View full text |Cite
|
Sign up to set email alerts
|

Embrittlement of uterus after uterine artery embolization: a case of uterine perforation

Abstract: Uterine artery embolization (UAE) is a common treatment for postpartum hemorrhage, however, the influences on uterus have yet to be uncertain. Here, we present a case of uterine embrittlement and perforation after UAE. A 30-year-old primipara received UAE for postpartum hemorrhage. Enhanced magnetic resonance imaging (MRI) after UAE showed lack of enhancement on uterine fundus. She complained hypomenorrhea after UAE, thus hysteroscopy was performed for intrauterine synechia. During the surgery, uterine perfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Accordingly, partial removal and in situ management are at risk for requiring uterine artery embolization or hysterectomy. Although obvious with hysterectomy, uterine artery embolization also has a risk for uterine necrosis and uterine rupture during a subsequent pregnancy due to uterine ischemia . Thus, local hemostasis should be performed if possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, partial removal and in situ management are at risk for requiring uterine artery embolization or hysterectomy. Although obvious with hysterectomy, uterine artery embolization also has a risk for uterine necrosis and uterine rupture during a subsequent pregnancy due to uterine ischemia . Thus, local hemostasis should be performed if possible.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine artery embolization is relatively less invasive than hysterectomy for postpartum hemorrhage, and therefore is increasingly used. However, this still has a risk for severe complications, including uterine necrosis and uterine rupture during a subsequent pregnancy . Thus, several hemostatic techniques have been developed for use in cesarean section .…”
Section: Introductionmentioning
confidence: 99%
“…This technique is considered useful for patients in whom various local hemostatic procedures have failed to control hemorrhage [28,29]. However, the association of TAE with prolonged uterine ischemia has become apparent, even when an absorbable embolus such as Spongel® is used [33,34]. The following complications of TAE have been reported: Asherman syndrome; infertility; ovarian dysfunction (increase in follicle-stimulating hormone levels); endometrial hypoplasia; menstruation disorders (e.g., amenorrhea, menstrual irregularity, oligomenorrhea, and hypomenorrhea); and pregnancy wastage, puerperal massive hemorrhage, placenta accreta, placenta previa, and uterine rupture in subsequent pregnancies [3,4,28,29,33,34].…”
Section: Interventional Radiologymentioning
confidence: 99%
“…It was suggested that these remaining ischemic areas had induced uterine rupture in the subsequent pregnancy. 9,20) The decision to employ TAE should not be made without careful deliberation, particularly in patients who wish to have a subsequent pregnancy; TAE should be saved as the last option. The use of TAE to prevent massive hemorrhage prior to treatment for cervical pregnancy, cesarean section scar pregnancy, puerperal pseudoaneurysm, or placental polyp should be avoided whenever possible.…”
Section: Arterial Embolizationmentioning
confidence: 99%